The Struggle of Local Religions to Deal with Discrimination in Religious Education: From Value Education to Social Movement - Nanang Hasan Susanto; Zaenal Mustakim; Imam Kanafi; Nur Kholis; Yayan Rahayani (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study intends to unravel aspects related to education in local religions. There are three (3) intercorrelated things regarding education in local religions, namely discrimination, value education, and social movements. Design/methods/approach – This study is qualitative research with a descriptive approach. The data source was obtained from the results of in-depth interviews and observations of members and traditional elders of three (3) local religions in Indonesia. The analysis used was a descriptive one. Findings – The three local religions studied often experience discrimination, especially in the aspect of education. This discrimination encourages them to spread the values education so that its existence continues to survive. The values education is an essential vehicle in carrying out social movements. Research implications/limitations – This study was limited to three local religions in Indonesia. The diversely abundant local religions in Indonesia allow for different dynamics between each other, related to discrimination in religious education, values education they uphold, and new social movements they bring about. Originality/value – The majority of scholars have studied various local religions to uncover their diverse religious teachings. Additionally, numerous studies also have discussed varied discriminations against religion. However, they are mostly related to discrimination in the aspect of citizenship rights that they should have. This research is more focused on discrimination in education, as well as the related elements, namely values education and new social movements, to overcome this discrimination.